PENINGKATAN DISIPLIN GURU DALAM MENGUMPULKAN PERANGKAT PEMBELAJARAN MELALUI SISTEM REWARD DAN PUNISHMENT SMAN 2 KINALI - Musfar Musfar (STKIP Pesisir Selatan, 2020)
Based on the results of observations made by researchers in the January-December semester 2019/2020, researchers found the phenomenon that the level of teacher discipline in collecting learning tools is still low. This can be seen from the time researchers asked teachers to collect learning tools. Many teachers did not collect the learning tools that were requested. There are also teachers who are in a hurry to prepare a learning kit when the Principal or supervisor will supervise the class. Of the 6 class teachers, if averaged, then only 60%, teachers who complete the learning tools in the form of syllabus, SK / KD analysis, lesson plans, prota promissory notes and teaching materials. Meanwhile, 40% of teachers do not collect. This research is a School Action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 6 Kinali SMAN 2 subject teachers who were research subjects teachers. Research data were collected using observation sheets. Data were analyzed using percentages. Based on the results of the study it can be concluded that the application of reward and punishment systems can improve teacher discipline in collecting learning tools. This is evidenced from before applying reward and punishment, the percentage of teachers who collected learning tools was only 66.67% with those who collected on time only amounted to 22.81%. After applying the reward and punishment system, in the first cycle, the teacher who collected the learning tools became 79.65% with the percentage who collected on time was 35.79%. After the second cycle, the percentage of teachers who collected learning tools became 97.54% with the percentage of teachers who collected on time amounted to 81.05%.